2014
DOI: 10.1371/journal.pone.0111715
|View full text |Cite|
|
Sign up to set email alerts
|

A Genome-Wide Association Study for Diabetic Retinopathy in a Japanese Population: Potential Association with a Long Intergenic Non-Coding RNA

Abstract: Elucidation of the genetic susceptibility factors for diabetic retinopathy (DR) is important to gain insight into the pathogenesis of DR, and may help to define genetic risk factors for this condition. In the present study, we conducted a three-stage genome-wide association study (GWAS) to identify DR susceptibility loci in Japanese patients, which comprised a total of 837 type 2 diabetes patients with DR (cases) and 1,149 without DR (controls). From the stage 1 genome-wide scan of 446 subjects (205 cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 50 publications
1
43
1
Order By: Relevance
“…A study in a cohort of Taiwanese type 2 diabetes patients and a meta-analysis of Japanese patients identified several loci reaching significance, but these findings have not been validated in an independent cohort [18,19]. None of the top loci in these studies appear to be replicated by other studies.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…A study in a cohort of Taiwanese type 2 diabetes patients and a meta-analysis of Japanese patients identified several loci reaching significance, but these findings have not been validated in an independent cohort [18,19]. None of the top loci in these studies appear to be replicated by other studies.…”
Section: Introductionmentioning
confidence: 74%
“…We first assessed loci reported in previous GWAS of diabetic retinopathy [15][16][17][18][19] for association in the current study in an attempt to replicate previous findings. A p value of <0.002 was required to account for the 29 loci assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS in diabetic retinopathy are emerging, and have suggested several loci related to diabetic retinopathy risk. For example, a Japanese study (<1000 cases and controls) reported associations between the long non-coding (lnc) RNA RP1-90L14 and susceptibility to diabetic retinopathy [281]. These studies are relatively small as measured by GWAS standard (ranging from several hundred to several thousand subjects), do not include optimally characterized subjects, and await validation.…”
Section: Gwas and Snpsmentioning
confidence: 99%
“…More specifically, the examined genes are likely involved in glucose-induced pathways, the metabolism of glucose and lipids, the inflammatory process, oxidative stress, tissue matrix remodeling, angiogenesis, and vascular endothelial dysfunction, or they are growth factors, cytoskeletal proteins, or parts of the renin-angiotensin aldosterone system (RAAS) [6][7][8][9]. Apart from CGAS, genome-wide association studies (GWAS) and linkage studies on patients with T2DM demonstrate a plausible association between genetic loci and DR or DN [10,11].…”
mentioning
confidence: 99%